Descripción de los principales métodos de control de Spodoptera frugiperda en el cultivo de maíz (Zea mays L) en la zona de Babahoyo, provincia de Los Ríos - Guerrero Aguirre, Kelvin Josué (2020)
Corn is one of the main grains grown in Ecuador. This grass has a vital meaning for the feeding of indigenous peoples; in addition to being considered a generator of life, which makes it a fundamental element of identity for our ancestors. In the country, this grain has been cultivated for centuries and is an important source of income for Ecuadorian families engaged in agriculture, chemical control is the most widely used practice to reduce populations of this insect. However, the products are generally used improperly or in doses sometimes lower than those recommended. Although much has been said and written about the origin of corn, there are still discrepancies regarding the details of its origin. Corn is generally considered to be one of the first plants cultivated by farmers 7,000 and 10,000 years ago. The earliest evidence of corn as a human food comes from some more archaeological sites where some small ears of corn estimated to be more than 5000 years old were found in caves of the primitive inhabitants. In Ecuador, a number of insect pests have been reported that cause damage to the corn crop. Of all of them, the most aggressive is the "heartworm" (Spodoptera frugiperda), which is a typical defoliator but behaves as a cutter, chopper and hearth. The small larvae destroy the epidermis of the leaves by feeding on its surface, leaving "scrapes", they also cut the corn seedlings at ground level. Large larvae devour foliage and penetrate the bud, where they hollow out and tear young corn tissue, and are potentially capable of damaging inflorescences.